Quadtree-based eigendecomposition for pose estimation in the presence of occlusion and background clutter - Saitwal, Kishor, author; Roberts, Rodney G., author; Balakrishnan, Venkataramanan, author; Maciejewski, Anthony A., author; Chang, Chu-Yin, author; Springer-Verlag London Limited, publisher (Colorado State University. Libraries, 2006)
Eigendecomposition-based techniques are popular for a number of computer vision problems, e.g., object and pose estimation, because they are purely appearance based and they require few on-line computations. Unfortunately, they also typically require an unobstructed view of the object whose pose is being detected. The presence of occlusion and background clutter precludes the use of the normalizations that are typically applied and significantly alters the appearance of the object under detection. This work presents an algorithm that is based on applying eigendecomposition to a quadtree representation of the image dataset used to describe the appearance of an object. This allows decisions concerning the pose of an object to be based on only those portions of the image in which the algorithm has determined that the object is not occluded. The accuracy and computational efficiency of the proposed approach is evaluated on 16 different objects with up to 50% of the object being occluded and on images of ships in a dockyard.
Keywords: partial occlusion; background clutter; singular value decomposition; object recognition; pose estimation; quadtree decomposition